Polymer blends for producing bidirectionally oriented polymer films

By preparing a polymer blend containing a specific polyethylene component and using a specific polymerization process, the complex structure and sustainability of bidirectional directed polymer films are solved, and high-performance and low-cost film preparation is achieved.

CN119816556APending Publication Date: 2025-04-11BASELL POLYOLEFINE GMBH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380063298.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-09-29
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, when preparing bidirectional directional polymer films, complex multilayer structures are difficult to meet the sustainability and recyclability requirements, and high-density polyethylene (HDPE) has difficulties in processing, resulting in insufficient final performance.

Method used

A polymer blend is provided, comprising 65% to 98% of the first polyethylene component and 2% to 35% of the second polyethylene component, polymerized by a specific melt index and density range, in combination with a Ziegler-Natta catalyst or a unit point catalyst, to prepare a bidirectional directional polymer film with good mechanical and aesthetic properties.

Benefits of technology

High mechanical properties (such as tensile modulus and fracture strength) and aesthetic properties (such as haze and gloss) of bidirectional directional polymer films are achieved, while simplifying the production process and reducing costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present disclosure relates to a polymer blend comprising: A) from 65% to 98% by weight of a first polyethylene component having: a density of from 0.948 g / cm3 to 0.960 g / cm3, a melt index MIF of from 30 g / 10 min to 100 g / 10 min, and a melt flow ratio MIF / MIP of from 15 to 30; and B) from 2% to 35% by weight of a second polyethylene component having a density from 0.910 g / cm < 3 > to 0.945 g / cm < 3 > and a melt index MIE from 0.1 g / 10 min to 3 g / 10 min.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a polymer blend, a method of using the same, a method of producing a biaxially oriented polymer film, and a biaxially oriented polymer film. Background Art

[0002] Polymer films are widely used in industrial manufacturing processes and in non-industrial industries for the delivery of goods to consumer markets at both wholesale and retail levels.

[0003] Currently, films composed of vinyl thermoplastic polymers dominate certain market applications, such as the household disposables, trash bags, and liner bags markets; overwrap films and bags for laundry and dry cleaning items; and shipping and take-out bags for retail sales of non-perishable goods. In other aspects of the consumer goods delivery market, vinyl polymer films are only slightly competitive, if at all, with other more expensive polymer films (such as plasticized polyvinyl chloride films and / or polypropylene films), such as in the heat shrink wrap film market for contour-wrapping various items (particularly perishable items such as meat, poultry, and fish). However, for other applications, such as packaging structures for packaging produce and grains, dry foods, and snacks, vinyl polymer films are somewhat competitive in some cases of these applications.

[0004] Biaxially oriented polymer films are increasingly in demand for packaging applications due to their valuable mechanical and optical properties.

[0005] However, to obtain optimal properties, biaxially oriented polymer films usually have a multilayer structure containing layers of different polymer materials, such as polypropylene, polyethylene, polyethylene terephthalate, polyamide, ethylene polyvinyl alcohol.

[0006] This complex structure requires sophisticated processing during membrane preparation and is difficult to comply with current sustainability and recyclability requirements.

[0007] Polyethylene, especially high-density polyethylene (HDPE), is an attractive candidate for preparing biaxially oriented films with low complexity in composition and structure.

[0008] In fact, HDPE can achieve high mechanical properties because it can be directionally stretched to relatively high draw ratios.

[0009] Furthermore, when properly processed, HDPE can acquire valuable optical properties.

[0010] However, the application of HDPE in the preparation of biaxially oriented films is severely limited due to processing difficulties, resulting in often insufficient final properties.

[0011] The object of the present disclosure is to provide a polymer blend, a method for using the same, a method for producing a biaxially oriented polymer film, and a biaxially oriented polymer film, which can at least partially overcome the disadvantages of the prior art and at the same time are simple and inexpensive to implement. Summary of the invention

[0012] Accordingly, the present disclosure provides a polymer blend comprising:

[0013] A) 65 to 98 wt% of a first polyethylene component having: 0.948 to 0.960 g / cm 3 A density of 100 g / 10 min, a melt index MIF of 30 g / 10 min to 100 g / 10 min, and a melt flow ratio MIF / MIP of 15 to 30 (particularly, up to 25); and

[0014] B) 2 to 35 wt% of a second polyethylene component having: 0.910 to 0.945 g / cm 3 The density is 0.1 g / 10 min to 3 g / 10 min, and the melt index MIE is 0.1 g / 10 min to 3 g / 10 min.

[0015] The above-mentioned weight % of the first polyethylene component and the above-mentioned weight % of the second polyethylene component are relative to the total weight (i.e., the sum of weights) of the first polyethylene component and the second polyethylene component. In some non-limiting cases, the above-mentioned weight % of the first polyethylene component and the above-mentioned weight % of the second polyethylene component are relative to the total weight of the polymer blend.

[0016] It has been experimentally observed that the present polymer blends allow obtaining biaxially oriented polymer films having surprisingly good mechanical properties (in particular tensile modulus and breaking strength) and aesthetic properties (in particular haze and gloss). DETAILED DESCRIPTION

[0017] In this document: MIF means melt index measured at 190°C using 21.6 kg; MIP means melt index measured at 190°C using 5 kg; MIE means melt index measured at 190°C using 2.16 kg.

[0018] The first polyethylene component A) and the second polyethylene component B) may be selected from ethylene homopolymers and ethylene copolymers containing α-olefin monomer units (preferably in an amount of up to 10% by weight) and mixtures thereof. Examples of such α-olefin monomer units are monomer units having 3 to 8 carbon atoms, in particular propylene, 1-butene, 1-pentene, 1-hexene, 1-octene and 4-methyl-1-pentene. 1-Butene and 1-hexene are preferred.

[0019] The homopolymers and copolymers can be obtained by a polymerization process in the presence of a coordination catalyst. The process and the homopolymers and copolymers obtained therefrom are widely described in the art.

[0020] In particular, the polymerization process may be carried out in the presence of a Ziegler-Natta catalyst or a single site catalyst.

[0021] As is known, Ziegler-Natta catalysts comprise the reaction product of an organometallic compound of Groups 1, 2 or 13 of the Periodic Table of Elements and a transition metal compound of Groups 4 to 10 of the Periodic Table of Elements (new numbering system). In particular, the transition metal compound may be selected from compounds of Ti, V, Zr, Cr and Hf, and is preferably supported on MgCl 2 superior.

[0022] Particularly preferred catalysts include an organometallic compound of Group 1, 2 or 13 of the Periodic Table of Elements and an organic metal compound supported on MgCl 2 The reaction product of the solid catalyst component on the Ti compound.

[0023] Preferred organometallic compounds are organo-Al compounds.

[0024] The single site catalysts are well known in the art and are typically selected from metallocene single site catalysts and non-metallocene single site catalysts.

[0025] Examples of metallocene single site catalysts are zirconocenes and hafnocenes, for example cyclopentadienyl or indenyl complexes of zirconium or hafnium, such as bis(cyclopentadienyl)zirconium dichloride; bis(indenyl)zirconium dichloride or bis(indenyl)hafnium dichloride.

[0026] Examples of non-metallocene single site catalysts are iron complexes preferably with tridentate ligands.

[0027] A particularly suitable tridentate ligand is 2,6-bis[1-(phenylimino)ethyl]pyridine and preferably the corresponding compounds in which both phenyl groups are substituted in the ortho position by halogen or tertiary alkyl substituents.

[0028] Specific examples are 2,6-bis[1-(2-tert-butylphenylimino)ethyl]pyridine iron (II) dichloride; 2,6-bis[1-(2-tert-butyl-6-chlorophenylimino)ethyl]pyridine iron (II) dichloride or 2,6-bis[1-(2,4-dichlorophenylimino)ethyl]pyridine iron (II) dichloride.

[0029] The metallocene single-site catalyst and the non-metallocene single-site catalyst may also be used in combination.

[0030] Preferably, the single site catalyst is reacted with an activating compound (cocatalyst), a preferred example of which is an aluminoxane, such as, for example, monomethylaluminoxane (MAO).

[0031] The polymerization can be carried out continuously or batchwise, in the presence of said catalyst, according to known techniques and in the liquid phase, in the presence or absence of an inert diluent, or in the gas phase or by liquid-gas mixing techniques.

[0032] Relative to the polymerization step, reaction time, pressure and temperature are not critical, however it is optimal if the temperature is from 50° C. to 100° C. The pressure may be atmospheric or higher.

[0033] The molecular weight is adjusted by using known regulators, in particular hydrogen.

[0034] The second polyethylene component B) may also consist of or comprise a low-density polyethylene (LDPE) selected from ethylene homopolymers or copolymers produced in high-pressure free-radical polymerization.

[0035] Examples of the LDPE copolymer include ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ethylene-acrylate copolymers, ethylene-methacrylate copolymers, ethylene copolymers containing α-olefin monomer units, and mixtures thereof.

[0036] Suitable examples of the α-olefin monomer unit in the LDPE copolymer are the same as described above.

[0037] There are two basic high-pressure polymerization processes for producing LDPE: the autoclave process and the tubular process.

[0038] LDPE produced using the autoclave reactor process has a high concentration of long chain branches, resulting in high tensile hardening values ​​and a relatively broad molecular weight distribution, making it easy to process.

[0039] The autoclave polymerization is generally carried out in the presence of a free radical initiator selected from organic peroxides.

[0040] The tubular reactor process does not necessarily require the use of organic peroxides. It can be carried out by using only oxygen as a free radical initiator, so LDPE can be prepared without chemical degradation products of organic peroxides.

[0041] The LDPE can also be prepared by a hybrid process combining both an autoclave reactor and a tubular reactor.

[0042] The process operating conditions may include, but are not limited to, a pressure in the range of 70 MPa to 700 MPa and a temperature in the range of 150°C to 500°C.

[0043] The polymerization may be carried out in the presence of one or more chain transfer agents known in the art, such as propylene, propane, and propionaldehyde.

[0044] Such chain transfer agents are used to adjust molecular weight.

[0045] Such processes and resulting LDPE products are well known in the art. For example, U.S. Patent No. 3,691,145 and U.S. Patent Application No. 2010 / 0076160 teach the production of LDPE in a tubular reactor process.

[0046] In general, the term "copolymer" is intended to also include polymers containing more than one comonomer, such as terpolymers.

[0047] All of the ethylene homopolymers and copolymers described are commercially available. Specific commercial polymers suitable for producing the present polymer blends are described in the examples.

[0048] Advantageously but not necessarily, the first polyethylene component has a tensile modulus of at least 650 MPa (particularly, at least 800 MPa; more particularly, at least 850 MPa). According to some non-limiting embodiments, the first polyethylene component has a tensile modulus of up to 1300 MPa (particularly, up to 1200 MPa; more particularly, up to 1100 MPa).

[0049] Advantageously, but not necessarily, the second polyethylene component has a tensile modulus of up to 1000 MPa, in particular up to 800 MPa. According to a particularly preferred embodiment, the second polyethylene component has a tensile modulus of up to 400 MPa, more in particular up to 300 MPa.

[0050] According to some non-limiting embodiments, the second polyethylene component has a tensile modulus of at least 100 MPa (specifically, at least 200 MPa; more specifically, at least 250 MPa).

[0051] Advantageously, but not necessarily, the second polyethylene component has a mass average molar mass Mw of less than 170,000 g / mol, in particular less than 160,000 g / mol.

[0052] According to a particularly preferred but non-limiting embodiment, the second polyethylene component has an Mw lower than 130000 g / mol (in particular, lower than 120000 g / mol).

[0053] In some non-limiting cases, the second polyethylene component has a Mw greater than 90,000 g / mol (specifically, greater than 100,000 g / mol).

[0054] Advantageously, but not necessarily, the second polyethylene component has a dispersity Mw / Mn lower than 22.0, in particular lower than 17.0.

[0055] According to a particularly preferred but non-limiting embodiment, the second polyethylene component has a Mw / Mn lower than 10.0, in particular lower than 8.0.

[0056] In some non-limiting cases, the second polyethylene component has a Mw / Mn greater than 5.0 (specifically, greater than 6.0).

[0057] According to some non-limiting embodiments, the second polyethylene component has a number average molar mass Mn higher than 9000 g / mol (particularly higher than 13000 g / mol); particularly, a number average molar mass Mn lower than 20000 g / mol (more particularly, lower than 17000 g / mol).

[0058] According to some non-limiting embodiments, the second polyethylene component has a number average molar mass Mz lower than 800000 g / mol (particularly lower than 400000 g / mol); particularly, higher than 200000 g / mol (more particularly, higher than 250000 g / mol).

[0059] Advantageously, but not necessarily, the first polyethylene component has a mass average molar mass Mw higher than 175000 g / mol, in particular higher than 185000 g / mol.

[0060] In some non-limiting cases, the first polyethylene component has a Mw of less than 250,000 g / mol (specifically, less than 210,000 g / mol).

[0061] Advantageously, but not necessarily, the first polyethylene component has a dispersity Mw / Mn higher than 22.0 (in particular, higher than 25.0; more in particular, higher than 26.0).

[0062] In some non-limiting cases, the first polyethylene component has a Mw / Mn of less than 34 (specifically, less than 30).

[0063] According to some non-limiting embodiments, the first polyethylene component has a number average molar mass Mz higher than 800000 g / mol (particularly higher than 900000 g / mol); particularly, lower than 150000 g / mol (more particularly, lower than 120000 g / mol).

[0064] According to some non-limiting embodiments, the first polyethylene component has a number average molar mass Mn lower than 9000 g / mol (particularly lower than 8000 g / mol); particularly, higher than 4000 g / mol (more particularly, higher than 6000 g / mol).

[0065] It has been experimentally observed that with a second polyethylene component having a relatively low tensile modulus and / or low Mw (and / or Mz) and / or Mw / Mn (see above) biaxially oriented polymer films having particularly good mechanical and aesthetic properties can be obtained.

[0066] Advantageously, but not necessarily, the first polyethylene component has a molecular weight of at least 0.950 g / cm 3 Alternatively or additionally, the second polyethylene component has a density of up to 0.940 g / cm 3 (Specifically, up to 0.930 g / cm 3 ) density. In some non-limiting cases, the second polyethylene component has a density of at least 0.915 g / cm 3 density.

[0067] Advantageously, but not necessarily, the first polyethylene component has a melt index MIF of 45 to 80 g / 10 min. Alternatively or additionally, the second polyethylene component has a melt index MIE of 0.6 to 2 g / 10 min.

[0068] Advantageously but not necessarily, the polymer blend comprises 67% to 95% by weight of the first polyethylene component, the above-mentioned weight % being relative to the total weight (i.e., the weight sum) of the first polyethylene component and the second polyethylene component. Additionally or alternatively, the polymer blend comprises up to 33% by weight (particularly, up to 25% by weight; more particularly, up to 15% by weight) of the second polyethylene component, the above-mentioned weight % being relative to the total weight (i.e., the weight sum) of the first polyethylene component and the second polyethylene component. In some cases, the polymer blend comprises at least 5% by weight (particularly, at least 10% by weight) of the second polyethylene component, the above-mentioned weight % being relative to the total weight (i.e., the weight sum) of the first polyethylene component and the second polyethylene component.

[0069] Advantageously, but not necessarily, the first polyethylene component has a melt index MIP of 0.5 g / 10 min (particularly 1.0 g / 10 min) to 15 g / 10 min (particularly 10 g / 10 min), particularly 1.0 g / 10 min to 10 g / 10 min.

[0070] According to some non-limiting embodiments, the polymer blend comprises:

[0071] - (from 1 wt. %; in particular, from 2 wt. %) up to 33 wt. % (in particular, up to 20 wt. %) of at least one third polyethylene component having: 0.920 g / cm3 to 0.950 g / cm 3 A density of 0.1 g / 10 min to 3 g / 10 min, a melt index MIE of 0.1 g / 10 min to 3 g / 10 min, and a tensile modulus of at least 400 MPa (particularly, at least 500 MPa);

[0072] - 65% to 98% by weight of the first polyethylene component, the above-mentioned weight % being relative to the total weight (i.e. the sum of the weights) of the first polyethylene component, the second polyethylene component and the third polyethylene component; and

[0073] 2 to 33 wt. % of a second polyethylene component, the wt. % being relative to the total weight (i.e. the sum of the weights) of the first, second and third polyethylene components, the second polyethylene component having a tensile modulus of up to 350 MPa (in particular, up to 300 MPa);

[0074] The weight % of the third polyethylene component is relative to the total weight (ie, the sum of the weights) of the first polyethylene component, the second polyethylene component, and the third polyethylene component.

[0075] According to a preferred but non-limiting embodiment, the weight percentage of the sum of the weights of the second polyethylene component and the third polyethylene component relative to the total weight (i.e. the sum of the weights) of the first polyethylene component, the second polyethylene component and the third polyethylene component is 3 weight % (in particular, 5 weight %) to 35 weight % (in particular, 33 weight %).

[0076] Additionally or alternatively, the third polyethylene component has a molecular weight of 0.920 g / cm3 to 0.950 g / cm 3 The third polyethylene component has a density of 0.1 g / 10 min to 3 g / 10 min, a melt index MIE of 0.1 g / 10 min to 3 g / 10 min, and an Mw lower than 170000 g / mol (particularly, lower than 160000 g / mol) and higher than 135000 g / mol (particularly, higher than 145000 g / mol; more particularly, higher than 150000 g / mol). In some non-limiting cases, the third polyethylene component has an Mw / Mn lower than 25 (particularly, lower than 22) and higher than 11 (particularly, higher than 12).

[0077] According to some non-limiting embodiments, the second polyethylene component has a Mw lower than 130,000 g / mol (particularly, lower than 120,000 g / mol).

[0078] It has been experimentally observed that the presence of both the second polyethylene component and the third polyethylene component allows to obtain biaxially oriented polymer films having surprisingly good aesthetic properties, in particular haze.

[0079] Advantageously but not necessarily, the weight % of the second polyethylene component is equal to or higher than the weight % of the third polyethylene component (the weight % of the third polyethylene component and the weight % of the second polyethylene component are relative to the total weight (i.e. the sum of the weights) of the first polyethylene component, the second polyethylene component and the third polyethylene component).

[0080] Advantageously, but not necessarily, the polymer blend contains 2% to 25% by weight (particularly, to 20% by weight; more particularly, to 15% by weight) of the second polyethylene component, the above-mentioned weight percentages being relative to the total weight (i.e. the sum of the weights) of the first polyethylene component, the second polyethylene component and the third polyethylene component.

[0081] Advantageously but not necessarily, the polymer blend contains 2% to 25% by weight (particularly, to 20% by weight; more particularly, to 15% by weight) of the third polyethylene component, the above-mentioned weight percentages being relative to the total weight (i.e. the sum of the weights) of the first polyethylene component, the second polyethylene component and the third polyethylene component.

[0082] According to a non-limiting example, the polymer blend consists of the first polyethylene component and the second polyethylene component (and optionally the third polyethylene component).

[0083] The polymer blends may also contain conventional additives.

[0084] Examples of these additives are heat stabilizers, antioxidants, UV absorbers, light stabilizers, metal deactivators, peroxide-destroying compounds and alkaline co-stabilizers, which are generally added in amounts of 0.01 to 10 wt %, preferably 0.1 to 5 wt %, based on the total weight of the polymer blend.

[0085] In another embodiment, a process for producing the above-mentioned polymer blend is provided herein. The process includes a combination step, during which the first polyethylene component and the second polyethylene component (and optionally the third polyethylene component) are combined by melting and mixing these components, and the mixing is carried out in a mixing device, and the temperature is generally 160° C. to 250° C.

[0086] Any known devices and techniques may be used for this purpose.

[0087] Melt mixing apparatuses useful in this context are in particular extruders or kneaders, particularly preferably twin-screw extruders. It is also possible to premix the components at room temperature in a mixing apparatus.

[0088] In another embodiment, provided herein is a method of using the polymer blend as described above for producing a biaxially oriented polymer film.

[0089] According to some embodiments, the use comprises a stretching step during which the film of the polymer blend is stretched in a first direction and a second direction that are crossed, in particular perpendicular, to each other.

[0090] Specifically, the film of the polymer blend is stretched in the first direction at a stretch ratio of 3: 1 to 9: 1. Additionally or alternatively, the film of the polymer blend is stretched in the second direction at a stretch ratio of 3: 1 to 7: 1.

[0091] In some non-limiting cases, the primary film before stretching has a thickness of at least 0.3 mm (particularly at least 0.5 mm), and the biaxially oriented polymer film has a thickness of less than 250 μm (particularly less than 100 μm; more particularly less than 50 μm).

[0092] In another embodiment, the present invention provides a method for producing a biaxially oriented polymer film, the method comprising a stretching step as disclosed above. Specifically, the polymer blend and the biaxially oriented polymer film are also disclosed above.

[0093] More specifically, but not necessarily, single-layer or multi-layer biaxially oriented films may be prepared using known techniques.

[0094] In particular, they can be prepared using a tenter process. In the tenter process, the polymer is extruded in the form of a film directly onto a chilled roll, which is then passed through a stretching unit by rollers that move faster than the extrusion speed of the polymer. This orients the film in the machine direction (MD).

[0095] Film extrusion is carried out using known techniques, preferably operating at a temperature of 180°C to 300°C.

[0096] In the orientation stage carried out in the stretching unit, the prevailing operating conditions are preferably:

[0097] - Preheating temperature: 120℃ to 130℃;

[0098] - Warm-up time: 60 to 100 seconds;

[0099] -Stretching rate: 40% / sec to 80% / sec;

[0100] -Stretching ratio: 3:1 to 9:1.

[0101] The film is then fed into a tenter frame for transverse orientation. In the tenter frame, the film is maintained at a preheat temperature and clamped along each edge by clamps attached to moving chains. These moving chains move outward to stretch the film in the transverse direction (TD). After stretching, the film is heat set to maintain orientation and then rolled up.

[0102] At this stage, the main operating conditions are preferably:

[0103] -Stretching rate: 30% / sec to 60% / sec;

[0104] -Stretching ratio: 3:1 to 7:1.

[0105] The biaxially oriented film can also be conveniently produced by the double bubble process. This process involves extruding the polymer components constituting the layers through an annular groove to produce a primary tubular film with concentric layers (when the film is multilayer). The primary film is calibrated and rapidly cooled, and then heated and oriented in the machine and transverse directions by blowing with compressed air (TD) and increasing the speed of the wind-up roll (MD). The biaxially oriented film is then rapidly cooled to stabilize the molecular orientation of the film.

[0106] In all of the processes described, heating may be performed by using, for example, IR lamps or hot air or other heating elements such as resistive heaters.

[0107] Biaxial orientation provides balanced mechanical properties. Biaxial film stretching greatly increases the tensile strength, flexibility, and toughness of the film. Orientation also enables the film to be used in heat shrink applications.

[0108] Patent application WO 97 / 22470 also discloses a method for producing an oriented film.

[0109] In another embodiment, provided herein is a biaxially oriented polymer film composed of the polymer blend disclosed above.

[0110] According to some non-limiting embodiments, the biaxially oriented polymer film has a thickness of less than 250 μm (specifically, less than 100 μm; more specifically, less than 50 μm).

[0111] Specifically, the biaxially oriented polymer film is obtained by the method described above.

[0112] Preferably, the biaxially oriented polymer film has one or more of the following properties:

[0113] - haze of 1.5% to 20%, more preferably 1.5 to 6.5;

[0114] - Film gloss (at 45°C): 45 GU to 100 GU;

[0115] - Tensile modulus MD: 700 MPa to 1600 MPa;

[0116] - Tensile modulus TD: 800 MPa to 1800 MPa;

[0117] - Breaking strength MD: 60MPa to 200MPa;

[0118] - Breaking strength TD: 130 MPa to 250 MPa;

[0119] - Elongation at break MD: 40% to 200%;

[0120] - Elongation at break TD: 40% to 200%.

[0121] Example

[0122] The practice and advantages of various embodiments, compositions and methods as provided herein are disclosed in the following examples below. These examples are merely illustrative and are not intended to limit the scope of the appended claims in any way.

[0123] The following analytical methods were used to characterize the polymer compositions.

[0124] Melt Flow Index

[0125] Measured according to ISO 1133-1 2012-03 at 190°C with a specified load.

[0126] density

[0127] Determined by immersion method at 23°C according to ISO 1183-1:2012.

[0128] Tensile modulus

[0129] Measured according to ASTM D882-18.

[0130] luster

[0131] Measured according to ASTM D-2457-13.

[0132] Haze

[0133] Measured according to ASTM D-1003-13.

[0134] Molecular weight distribution determination

[0135] The average values ​​of Mw, Mn, Mz and the Mw / Mn derived therefrom were determined by high temperature gel permeation chromatography using the method described in ISO 16014-1, -2, -4 published in 2003. According to the ISO standard, the details are as follows: solvent 1,2,4-trichlorobenzene (TCB), temperature of the apparatus and solution 145°C, and a PolymerChar (Valencia, Paterna 46980, Spain) IR-4 infrared detector that can be used with TCB as a concentration detector. A WATERS Alliance 2000 equipped with the following precolumn SHODEX UT-G and separation columns SHODEX UT 806M (3 pieces) and SHODEX UT 807 (Showa Denko Europe GmbH, Konrad-Zuse-Platz 4, 81829 Muenchen, Germany) connected in series was used.

[0136] The solvent was vacuum distilled under nitrogen and stabilized with 0.025 wt% 2,6-di-tert-butyl-4-methylphenol. The flow rate used was 1 ml / min, the injection volume was 500 μl, and the polymer concentration was in the range of 0.01% < concentration < 0.05% w / w. Molecular weight calibration was established by using monodisperse polystyrene (PS) standards in the range of 580 g / mol to 11 600 000 g / mol from Polymer Laboratories (now Agilent Technologies, Herrenberger Str. 130, 71034 Boeblingen, Germany) and additionally using hexadecane.

[0137] The calibration curve was then adapted to polyethylene (PE) by the universal calibration method (Benoit H., Rempp P. and Grubisic Z., J. Polymer Sci., Phys. Ed., 5, 753 (1967)). The Mark-Houwing parameters for PS used here are: k PS =0.000121dl / g, α PS =0.706, and for PE, k PE =0.000406dl / g, α PE= 0.725, valid in TCB at 135° C. Data recording, calibration and calculation were performed using NTGPC_Control_V6.02.03 and NTGPC_V6.4.24 (hs GmbH, Hauptstraβe 36, D-55437 Ober-Hilbersheim, Germany), respectively.

[0138] Comonomer content

[0139] The comonomer content was determined by IR according to ASTM D 6248 98 using a FT-IR spectrometer Tensor 27 from Bruker calibrated with a stoichiometric model for the determination of ethyl side chains in PE (with 1-butene as comonomer) and butyl side chains in PE (with 1-hexene as comonomer).

[0140] Example 1

[0141] This example discloses the preparation of samples of biaxially oriented polymer films and the properties of the resulting films.

[0142] The following commercially available starters sold by LyondellBasell Industries were used.

[0143] Hostalen GD 9555(GD9555)

[0144] -MIP: 3.0 g / 10 min;

[0145] -MIF: 63g / 10min;

[0146] -Density: 0.953g / cm 3 ;

[0147] -Tensile modulus: 1050 MPa;

[0148] - Yield tensile stress: 25MPa;

[0149] - Tensile strain at yield: 10%.

[0150] Luflexen hyPE 35P FA(hyPE)

[0151] -MIE: 0.75g / 10min;

[0152] -Density: 0.936g / cm 3 ;

[0153] -Tensile modulus: 600 MPa;

[0154] - Tensile stress at yield: 16MPa.

[0155] Lupolen 2420F(LP 2420F)

[0156] -MIE: 0.75g / 10min;

[0157] -Density: 0.923g / cm 3 ;

[0158] -Tensile modulus: 260 MPa;

[0159] - Tensile stress at yield: 11MPa.

[0160] The molecular weights are shown in Table 1 below.

[0161] Table 1

[0162] GD 9555 hyPE 35PFA LP 2420F Mn[g / mol] 7116 11161 15288 Mw[g / mol] 195382 155288 110236 Mw / Mn 27.46 13.91 7.21 Mz[g / mol] 1078110 519473 318406

[0163] Samples of biaxially oriented polymer films were prepared having the following polymer blends (percentages are by weight relative to the total weight of the polymer blend).

[0164] -A: 100% GD9555

[0165] -B: 90% GD9555+10% hyPE

[0166] -C: 90% GD9555+10% LP 2420F

[0167] -D: 80% GD9555+10% hyPE+10% LP 2420F

[0168] -E: 70% GD9555+15%hyPE+15% LP 2420F

[0169] To obtain the biaxially oriented polymer film, the following procedure was employed.

[0170] A primary film having a thickness of 1 mm was produced under the following conditions using a Leonard production line having the following characteristics:

[0171] - Extruder diameter: 40mm, L / D 27;

[0172] - Fixed displacement gear pump;

[0173] - Flat die, die lip width 200mm, die lip gap 1mm;

[0174] - Melting temperature: 240°C;

[0175] - 3 cooling rollers, diameter 160mm, roller temperature 45℃;

[0176] - Film cutting unit.

[0177] 93 mm x 93 mm specimens were cut from the primary film. These specimens were then oriented using a Brueckner KARO IV stretching unit under the following conditions:

[0178] -Preheating temperature: 123°C;

[0179] -Heating time: 80 seconds;

[0180] -Stretching speed: 45% / sec to 60% / sec;

[0181] -Stretching area: 70mmx70mm (outside the fixture);

[0182] -Stretching ratio: MD 6:1; TD 5:1;

[0183] - Final thickness: 23 μm.

[0184] The prepared biaxially oriented polymer film had the properties shown in Table 2 below.

[0185] Table 2

[0186] characteristic unit A B C D E Film haze % 6.8 6.2 5.2 4.0 3.6 Film gloss (at 45°C) GU 68.5 80.4 79.2 81.7 82.3 Tensile modulus MD MPa 1026 1205 1367 1112 1020 Tensile modulus TD MPa 1460 1640 1713 1467 1410 Breaking Strength MD MPa 128 164 168 158 144 Elongation at break MD % 83 105 90 84 89 Breaking strength TD MPa 147 181 197 190 173 Elongation at break TD % 60 60 86 80 70

[0187] MD stands for "machine direction." In other words, this means that the measurement is made in the direction of extrusion.

[0188] TD stands for in the "transverse direction." In other words, this means that the measurement is made in a direction substantially perpendicular to the extrusion direction.

[0189] Prior to these tests, one skilled in the art would have believed that adding a polymer having a low density to a base polymer having a high density would provide a biaxially oriented polymer film having significantly lower mechanical properties, particularly tensile modulus and breaking strength.

[0190] The results obtained are therefore truly surprising: contrary to what would be expected in most cases, an improvement is achieved; or at least only a slight deterioration.

Claims

1. A polymer blend, comprising: A) 65 to 98 wt% of a first polyethylene component having: 0.948 to 0.960 g / cm 3 A density of 30 g / 10 min to 100 g / 10 min, a melt index MIF of 30 g / 10 min to 100 g / 10 min, and a melt flow ratio MIF / MIP of 15 to 30; and B) 2 to 35 wt% of a second polyethylene component having: 0.910 to 0.945 g / cm 3 The density is 0.1 g / 10 min to 3 g / 10 min, and the melt index MIE is 0.1 g / 10 min to 3 g / 10 min. The weight percent of the first polyethylene component and the weight percent of the second polyethylene component are relative to the total weight of the first polyethylene component and the second polyethylene component.

2. The polymer blend of claim 1, wherein the first polyethylene component has a tensile modulus of at least 650 MPa.

3. The polymer blend of claim 1 or 2, wherein the second polyethylene component has a tensile modulus of at least 100 MPa.

4. The polymer blend according to any one of the preceding claims, wherein the second polyethylene component has an Mw below 170,000 g / mol and an Mw / Mn below 22; and the first polyethylene component has an Mw above 175,000 g / mol and an Mw / Mn above 22.

5. The polymer blend according to any one of the preceding claims, wherein the first polyethylene component has a molecular weight of at least 0.950 g / cm 3 The second polyethylene component has a density of 0.915g / cm 3 To a density of 0.940g / cm3.

6. The polymer blend according to any one of the preceding claims, wherein the first polyethylene component has a melt index MIF of 45 to 80 g / 10 min; and the second polyethylene component has a melt index MIE of 0.6 to 2 g / 10 min.

7. A polymer blend according to any one of the preceding claims, comprising: 67 wt% to 95 wt% of the first polyethylene component, the wt% being relative to the total weight (i.e. the sum of the weights) of the first polyethylene component and the second polyethylene component; and 5 wt% to 33 wt% of the second polyethylene component, the wt% being relative to the total weight (i.e. the sum of the weights) of the first polyethylene component and the second polyethylene component; the first polyethylene component having a melt index MIP of 0.5 g / 10 min to 15 g / 10 min.

8. The polymer blend according to any one of the preceding claims, comprising: - Up to 33% by weight of at least one third polyethylene component having: 0.920 g / cm3 to 0.950 g / cm 3 A density of 0.1 g / 10 min to 3 g / 10 min, a melt index MIE of 0.1 g / 10 min to 3 g / 10 min, and a tensile modulus of at least 400 MPa; - 65% to 98% by weight of the first polyethylene component, the weight % being relative to the total weight of the first polyethylene component, the second polyethylene component and the third polyethylene component; and - 2 to 33 wt% of the second polyethylene component, the wt% being relative to the total weight of the first polyethylene component, the second polyethylene component and the third polyethylene component, the second polyethylene component having a tensile modulus of up to 350 MPa; The weight percent of the third polyethylene component is relative to the total weight of the first polyethylene component, the second polyethylene component and the third polyethylene component; Provided that the weight % of the sum of the weight of the second polyethylene component and the third polyethylene component relative to the total weight of the first polyethylene component, the second polyethylene component and the third polyethylene component is 3 wt % to 35 wt %.

9. The polymer blend according to any one of the preceding claims, comprising: - Up to 33% by weight of at least one third polyethylene component having: 0.920 g / cm3 to 0.950 g / cm 3 A density of 0.1 g / 10 min to 3 g / 10 min, a melt index MIE of 0.1 g / 10 min to 3 g / 10 min, a Mw of less than 170,000 g / mol and greater than 135,000 g / mol, and a Mw / Mn of less than 22 and greater than 11; - 65% to 98% by weight of the first polyethylene component, the weight % being relative to the total weight of the first polyethylene component, the second polyethylene component and the third polyethylene component; -2 to 33 wt% of the second polyethylene component, the wt% being relative to the total weight of the first polyethylene component, the second polyethylene component and the third polyethylene component, the second polyethylene component having an Mw lower than 130,000 g / mol and an Mw / Mn lower than 10; - the weight % of the third polyethylene component is relative to the total weight of the first polyethylene component, the second polyethylene component and the third polyethylene component; - provided that the weight % of the sum of the weight of the second polyethylene component and the third polyethylene component relative to the total weight of the first polyethylene component, the second polyethylene component and the third polyethylene component is 3 wt% to 35 wt%.

10. The polymer blend according to claim 8 or 9, wherein the weight % of the second polyethylene component is equal to or higher than the weight % of the third polyethylene component; the weight % of the third polyethylene component and the weight % of the second polyethylene component are relative to the total weight of the first polyethylene component, the second polyethylene component and the third polyethylene component.

11. A method of using a polymer blend according to any one of the preceding claims for producing a biaxially oriented polymer film.

12. The method according to claim 11, comprising a stretching step during which the primary film of the polymer blend is stretched in two directions crossing each other.

13. A method for producing a biaxially oriented polymer film; the method comprising a stretching step, during which a primary film of the polymer blend according to any one of claims 1 to 10 is stretched in two directions crossing each other to obtain the biaxially oriented polymer film.

14. The method of claim 13, wherein the primary film of the polymer blend has a thickness of at least 0.3 mm and the biaxially oriented polymer film has a thickness of less than 250 μm.

15. A biaxially oriented polymer film consisting of or comprising the polymer blend according to any one of claims 1 to 10.

16. The biaxially oriented polymer film of claim 15, having a thickness of less than 250 μm.

Citation Information

Patent Citations

  • Modifying tubular LDPE with free radical initiator

    US20100076160A1

  • Production of polyethylene by the high pressure process using a mixture of tertiary butyl hydroperoxide and oxygen as the initiator

    US3691145A

  • Biaxially oriented polyethylene films

    WO1997022470A1